Functional variants in HCN4 and CACNA1H may contribute to genetic generalized epilepsy. Issue 3 (5th August 2017) - Becker, Felicitas; Reid, Christopher A.; Hallmann, Kerstin; Tae, Han‐Shen; Phillips, A. Marie; Teodorescu, Georgeta; Weber, Yvonne G.; Kleefuss‐Lie, Ailing; Elger, Christian; Perez‐Reyes, Edward; Petrou, Steven; Kunz, Wolfram S.; et al.
Summary: Objective: Genetic generalized epilepsy (GGE) encompasses seizure disorders characterized by spike‐and‐wave discharges (SWD) originating within thalamo‐cortical circuits. Hyperpolarization‐activated (HCN) and T‐type Ca 2+ channels are key modulators of rhythmic activity in these brain regions. Here, we screened HCN4 and CACNA1H genes for potentially contributory variants and provide their functional analysis. Methods: Targeted gene sequencing was performed in 20 unrelated familial cases with different subtypes of GGE, and the results confirmed in 230 ethnically matching controls. Selected variants in CACNA1H and HCN4 were functionally assessed in tsA201 cells and Xenopus laevis oocytes, respectively. Results: We discovered a novel CACNA1H (p.G1158S) variant in two affected members of a single family. One of them also carried an HCN4 (p.P1117L) variant inherited from the unaffected mother. In a separate family, an HCN4 variant (p.E153G) was identified in one of several affected members. Voltage‐clamp analysis of CACNA1H (p.G1158S) revealed a small but significant gain‐of‐function, including increased current density and a depolarizing shift of steady‐state inactivation. HCN4 p.P1117L and p.G153E both caused a hyperpolarizing shift in activation and reduced current amplitudes, resulting in a loss‐of‐function. Significance: Our results are consistent with a model suggesting cumulative contributions of subtle functional variations in ion channels to seizure susceptibility and GGE.